5-Fluoro-2-(4-iodophenyl)-3-methylsulfinyl-1-benzofuran - Hong Dae Choi; Pil Ja Seo; Byeng Wha Son; Uk Lee (Acta Crystallographica Section E, 2009)
In the title compound, C15H10FIO2S, the O atom and the methyl group of the methylsulfinyl substituent lie on opposite sides of the plane through the benzofuran fragment. The 4-iodophenyl ring is rotated out of the benzofuran plane by a dihedral angle of 39.4 (1)°. The crystal structure is stabilized by an intermolecular C—H...O hydrogen bond and an I...O halogen bond [3.055 (2) Å]. The crystal structure also exhibits an intermolecular C—H...π interaction between the methyl H atom and the 4-iodophenyl ring of an adjacent benzofuran molecule, and aromatic π–π interactions between the benzene rings of neighbouring benzofuran systems [centroid–centroid distance = 3.558 (3) Å].